Evaluation of colour in Serra da Estrela cheese produced in different dairies along maturation time - Guiné, Raquel (2019)
“Serra da Estrela” cheese is a Portuguese traditional cheese with Protected Designation of Origin (PDO), and with a major importance in the national cheese making history. Due to its particular sensory characteristics, namely intense flavour, taste and aroma allied with a smooth texture, it is nowadays one of the most valued products both in Portugal and also abroad. The objective of this work was to compare the colour of Serra da Estrela Cheese manufactured in different dairies and to evaluate the changes that take place along the production season. The samples used for the study were obtained from 6 dairies situated in PDO region for this cheese. The colour measurements were made with a colorimeter in CIELAB coordinates: L*a*b*. To evaluate the colour change during milking season, the colour difference was also calculated. The results obtained in this work indicated that the colour characteristics of the Serra da Estrela Cheeses are slightly different between samples coming from different dairies where the cheeses are manufactured. Nevertheless, in the first moment of the evaluation period, the values of the colour coordinates varied in a limited range, which means that the variations could be considered acceptable attending to the nature of the traditional manufacture process associated with this PDO product. Furthermore, the results showed that along season very important changes in colour took place, which might be expected having in mind the nature of the physical-chemical changes produced in the pastures along time. However, these changes were found very much dependent of the dairy, as the results of total colour change demonstrated.